(untitled) (Academicia Globe: Inderscience Research, 2022)
Male white (laboratory) rats were used at a rate of (24) rats, ages ranged between (1.5-2) months, and average weights ranged between (150-200) grams. The animals were obtained from the animal house / College of Veterinary Medicine - Tikrit University, The carcinogen dissolved in olive oil was dosed to rats by oral administration at a rate of 1 ml and in two doses, each dose 0.5 ml of the carcinogen. The second dose is given three days after giving the first dose.